2018
DOI: 10.25135/acg.oc.42.18.03.070
|View full text |Cite
|
Sign up to set email alerts
|

Towards 3-(2-adamantylidene)diamantane derivatives through the McMurry cross coupling reaction

Abstract: Diamondoid assemblies have a potential in nanoelectronics as the substrates for self-assembled monolayer formation. However, selective functionalization of such molecules is cumbersome. We demonstrate that the McMurry cross-coupling reaction is useful for the preparation of 3-(2-adamantylidene)diamantane derivatives with substituents at the tertiary and secondary positions of the diamantane moiety. This allows to create the surface attachment points in the diamondoid structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In 2018, A novel synthetic of diamondoids compound, especially adamantane, 190, has also been reached by Hoc et al using the McMurry reaction. 104 Diamondoid is an unusual molecule that has been widely applied in geochemistry since 1990 due to its peculiar cage molecular structure. Both diamondoid and its derivatives are contained naturally in oil and fossil deposits with a 1–100 ppm concentration.…”
Section: Applications Of the Mcmurry Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, A novel synthetic of diamondoids compound, especially adamantane, 190, has also been reached by Hoc et al using the McMurry reaction. 104 Diamondoid is an unusual molecule that has been widely applied in geochemistry since 1990 due to its peculiar cage molecular structure. Both diamondoid and its derivatives are contained naturally in oil and fossil deposits with a 1–100 ppm concentration.…”
Section: Applications Of the Mcmurry Reactionmentioning
confidence: 99%
“…Both diamondoid and its derivatives are contained naturally in oil and fossil deposits with a 1–100 ppm concentration. 104 The low series of diamondoids plays a vital role in designing and synthesizing drug delivery systems. The experimental results showed that the McMurry coupling of diamantanone and amantanone was successful with high product yields.…”
Section: Applications Of the Mcmurry Reactionmentioning
confidence: 99%